1998
DOI: 10.1029/97jd03545
|View full text |Cite
|
Sign up to set email alerts
|

Electrical structure in thunderstorm convective regions: 3. Synthesis

Abstract: Abstract. In this paper, results from nearly 50 electric field soundings through convective regions of mesoscale convective systems (MCSs), isolated supercelIs, and isolated New Mexican mountain storms are compared and synthesized. These three types of thunderstorm convection are found to have a common, basic electrical structure. Within convective updrafts the basic charge structure has four charge regions, alternating in polarity, and the lowest is positive. Outside updrafts of convection there are typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 48 publications
10
145
0
8
Order By: Relevance
“…The prior discussion assumes a simple electric dipole storm structure; however, the real world is obviously more complex [e.g., Stolzenburg et al, 1998]. For the case presented here, there are two distinct convective pulses.…”
Section: 1002/2015jd023383mentioning
confidence: 99%
“…The prior discussion assumes a simple electric dipole storm structure; however, the real world is obviously more complex [e.g., Stolzenburg et al, 1998]. For the case presented here, there are two distinct convective pulses.…”
Section: 1002/2015jd023383mentioning
confidence: 99%
“…Lower positive charge was evident in the cloud between 4.3 and 5.1 km [e.g., Marshall and Winn, 1982]. Negative charge was located between 5.2 and 5.8 km [e.g., Stolzenburg et al, 1998c]. Above 5.8 km, it is more difficult to identify the charge regions, except for the uppermost positive charge between 7.3 and 7.7 km, which seems to be a screening charge at the upper cloud boundary [e.g., Marshall et al, 1989;Marshall and Rust, 1991].…”
Section: Flash Amentioning
confidence: 99%
“…Their measurements indicated that IC flashes begin with ''upward propagating negative breakdown'' followed ''after a time delay'' by radiation associated with previously undetected positive polarity breakdown. Presumably, the two polarities of breakdown were initially driven by the primarily downward pointing electric field (E) commonly seen between the main negative and upper positive charge regions [e.g., Winn et al, 1978;Stolzenburg et al, 1998aStolzenburg et al, , 1998bStolzenburg et al, , 1998c. Shao and Krehbiel [1996] assumed that the horizontal branches of the bilevel IC flashes traveled through the main negative and upper positive charge regions of the cloud.…”
Section: Introductionmentioning
confidence: 99%
“…The lighter hydrometeors are transported upward, the heaviest being sustained at lower altitude in the cloud. Combined with cloud dynamics and cloud microphysics, electrification processes lead to dipoles, tripoles and even stacks of charged zones vertically distributed in the thundercloud (Stolzenburg et al, 1998;Rust et al, 2005). Between the charged regions, the ambient electric field can reach very high values, i.e., more than 100 kV m −1 (Marshall et al, 2005).…”
Section: Introductionmentioning
confidence: 99%